PERSEPSI PERAWAT DAN MANAJER TENTANG MODEL PENUGASAN KEPERAWATAN - Gita Adelia; Setiawan Setiawan; Roymond H Simamora (LPPM STIKES KENDAL, 2019)
The nursing delivery model is described as a structured approach to regulating the provision of nursing care to patients to facilitate nurses in prioritizing nursing care to be provided. This study aims to explore the perceptions of nurses and managers about the nursing delivery model in the inpatient ward of the University of North Sumatra. The design of this study is qualitative research with a phenomenological approach. The number of samples used is as many as 12 participants taken through purposive sampling technique. The results of the study obtained three thematic categories: 1) the nursing delivery model used in the inpatient room, 2) the advantagesof the nursing delivery model used, 3) the disadvantages of the nursing delivery model used. Conclusion: It is necessary to strengthen the nursing model of the team in the University of North Sumatra hospital hospitalization